2018
DOI: 10.1007/s10286-018-0577-0
|View full text |Cite
|
Sign up to set email alerts
|

Functional neuroimaging of the central autonomic network: recent developments and clinical implications

Abstract: PurposeThe central autonomic network (CAN) is an intricate system of brainstem, subcortical, and cortical structures that play key roles in the function of the autonomic nervous system. Prior to the advent of functional neuroimaging, in vivo studies of the human CAN were limited. The purpose of this review is to highlight the contribution of functional neuroimaging, specifically functional magnetic resonance imaging (fMRI), to the study of the CAN, and to discuss recent advances in this area. Additionally, we … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
80
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 113 publications
(81 citation statements)
references
References 101 publications
(151 reference statements)
1
80
0
Order By: Relevance
“…These findings are consistent with previously reported structural and functional abnormalities in cluster headache patients, which have helped to shed light on their possible pathologic roles. In CH patients, the precentral gyrus was found to have decreased cortical thickness (Cosentino et al, 2015;Seifert et al, 2012). It has also been reported that CH patients possessed decreased gray matter volume in structures in the pain-matrix network, notably the precentral gyrus, insula, and inferior parietal lobe (Absinta et al, 2012).…”
Section: Discussionmentioning
confidence: 90%
See 1 more Smart Citation
“…These findings are consistent with previously reported structural and functional abnormalities in cluster headache patients, which have helped to shed light on their possible pathologic roles. In CH patients, the precentral gyrus was found to have decreased cortical thickness (Cosentino et al, 2015;Seifert et al, 2012). It has also been reported that CH patients possessed decreased gray matter volume in structures in the pain-matrix network, notably the precentral gyrus, insula, and inferior parietal lobe (Absinta et al, 2012).…”
Section: Discussionmentioning
confidence: 90%
“…Within the pain-matrix network, the ACC and insula are thought to be centers for affective components of pain processing and perception and modulation of pain, respectively (Fuchs et al, 2014 ; Lu et al, 2016 ). Within the central autonomic network, the ACC, insula, and several brain stem regions are key nodes in the autonomic nervous system function (Sklerov et al, 2018 ). Streamlines to the precentral gyrus and the inferior parietal lobe were prominent with our parameters.…”
Section: Discussionmentioning
confidence: 99%
“…To the researchers' knowledge, no previous study has investigated the influence of HRV BFB or any paced breathing technique on neuromuscular responses. An enhancement in baroreflex with HRV BFB might positively influence activity in the central autonomic network and facilitate improvement in neural excitability [1,[13][14][15][16][17][18][19][20]. Accordingly, neural excitability of the alpha motoneural pool could be revealed by the determination of the Hoffman reflex (H-reflex), a monosynaptic reflex in the spinal cord [21][22][23][24][25].…”
Section: Introductionmentioning
confidence: 99%
“…In this issue of Clinical Autonomic Research, Sklerov and colleagues, at the University of North Carolina, have written a very comprehensive review on the state-of-the art of human brain imaging of the central autonomic network [3]. It covers the methodological aspects and, based on a metaanalysis of studies that have used brain imaging to study the human central autonomic network, provides a useful summary of the key areas of the brain involved in cardiovascular control at rest and during maneuvers known to increase muscle sympathetic nerve activity.…”
mentioning
confidence: 99%